Low-energy electron scattering from molecular hydrogen: Excitation of the X 1 Sg+ to b 3 Su+ transition - Zawadzki, M.; Wright, R.; Dolmat, G.; Martin, M.; Diaz, B.; Hargreaves, L.; Coleman, D.; Fursa, Dmitry; Zammit, M.; Scarlett, Liam; Tapley, J.; Savage, J.; et al. (2018)
We present time-of-flight differential cross-section measurements and convergent close-coupling calculations of differential cross sections for the electron-impact excitation of the XSg+1?bSu+3 transition in molecular hydrogen. A part of this work was recently published [M. Zawadzki, Phys. Rev. A 97, 050702(R) (2018)10.1103/PhysRevA.97.050702]. In this work, agreement between theory and experiment is excellent overall, and marks a transition in electron-molecule scattering where differential scattering of excitation is found to be in such precise agreement. We also present total electron-impact excitation differential cross sections for H2 for which agreement between theory and experiment is found to be excellent.